Inferring the Lifetime of Endosomal Protein Complexes by Fluorescence Recovery after Photobleaching - Gousseva, Veronika (The Biophysical Society, 2008)
Cellular signal transduction is dynamic, with signaling proteins continually associating and dissociating into and from protein complexes. Here we present a fluorescence recovery after photobleaching technique to determine the lifetime of protein complexes on intracellular vesicles. We use Bayesian inference based on a model that includes the diffusion of cytosolic proteins and their interaction with membrane-bound receptors. Our analysis is general: we incorporate prior information on protein diffusion, measurement error in determining fluorescence intensities, corrections for photobleaching, and variation in the concentration of receptors between vesicles. We apply our method to the complexes formed on endosomes by G-protein-coupled receptors and the protein β-arrestin. The lifetime of these complexes determines the recycling rate of the receptors. We find in mammalian cells that the bradykinin type 2 receptor and β-arrestin2 complex has a lifetime of ∼2 min, while the angiotensin II type 1A receptor and β-arrestin2 complex has a lifetime of ∼6 min. As well as allowing quantitative comparisons between experiments, our method provides in vivo parameters for systems biology simulations of signaling networks.